Research and Application of Heat Treatment Process with 20Cr13 Martensitic Stainless Steel Material for Chain - Zhang Jiancong; Wang Lili; Huang Jia (Jixie chuandong)
View of the fracture problem of the chain in the 20Cr13 material of martensitic stainless steel,the scheme of improving the heat treatment process is put forward. Through the test of the different parameters of heat treatment,comprehensive the hardness and Charpy impact test,the appropriate heat treatment process is determined. The practice shows that,according to the results of the above scheme,the design of the chain meets the requirements of corrosion resistance,wear resistance and higher strength.